Prevalence of aggressive periodontitis in 15-18 years old schoolgirls in Tehran, Iran - Sadeghi R; Semiari H; Aziz T; Abedi P; Khodaverdi A; Reeyazi S (Tehran University of Medical Sciences, 2006)
Background and Aim: Aggressive periodontitis is one of the periodontal diseases, which affects systemically healthy individuals usually under the age of 30 years old. The disease is characterized by rapid bone destruction which is not in accordance with the quantity of bacterial plaque. The purpose of the present study was to determine the prevalence of aggressive periodontitis among 15-18 years old female students in Tehran high schools. Materials and Methods: In this cross sectional study, , 2870 students were selected from all educational areas of Tehran during 1382-83 based on systematic clustered random sampling .Probing pocket depth on 6 areas of incisors and first molars were examined in each subject. Students with pocket depth equal to or more than 4 mm on more than one tooth were referred to Shahed Dental School for radiographic examination. For cases in which the distance between the crest of interdental septa and CEJs were equal to or more than 2 mm, full clinical and radiographic examination was performed. Results: Among the subjects of study, only 4 fulfilled the diagnostic criteria of localized aggressive periodontitis. Nobody was diagnosed with generalized aggressive periodontitis. The prevalence of aggressive periodontitis among 15-18 years old schoolgirls was 0.14%. Conclusion: The results of the present study were similar to previous studies with the same age groups and diagnostic criteria in other countries. For determination of total prevalence in Tehran, similar studies in schoolboys are recommended.